2003
DOI: 10.2165/00003495-200363090-00002
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Postoperative Pain Management in the Ambulatory Patient

Abstract: Over 60% of surgery is now performed in an ambulatory setting. Despite improved analgesics and sophisticated drug delivery systems, surveys indicate that over 80% of patients experience moderate to severe pain postoperatively. Inadequate postoperative pain relief can prolong recovery, precipitate or increase the duration of hospital stay, increase healthcare costs, and reduce patient satisfaction. Effective postoperative pain management involves a multimodal approach and the use of various drugs with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
85
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 62 publications
0
85
0
10
Order By: Relevance
“…Os gastos associados a essa condição de saúde estimulam o sistema a investigar intervenções eficazes para o tratamento das dores em geral (7) . O tratamento clássico da dor (aguda) consiste em repouso e uso de fármacos para o alívio do sintoma, para favorecer a cicatrização da lesão (8) e a redução do processo inflamatório (9) . Ao contrário do tratamento da dor aguda, os agentes químicos analgésicos não se demonstram eficazes contra a dor crônica (10,11) .…”
Section: Introductionunclassified
“…Os gastos associados a essa condição de saúde estimulam o sistema a investigar intervenções eficazes para o tratamento das dores em geral (7) . O tratamento clássico da dor (aguda) consiste em repouso e uso de fármacos para o alívio do sintoma, para favorecer a cicatrização da lesão (8) e a redução do processo inflamatório (9) . Ao contrário do tratamento da dor aguda, os agentes químicos analgésicos não se demonstram eficazes contra a dor crônica (10,11) .…”
Section: Introductionunclassified
“…However, opioid use is frequently accompanied by opioid-related adverse drug events (ORADEs) and other negative consequences, including increased mortality. 6,7 Wheeler et al (2002) found that 29.0% of preventable adverse drug events (ADEs) were associated with analgesic use, the majority of which included opioids. 8 The most common of these ORADEs include gastrointestinal (GI) effects such as constipation, ileus, nausea, and vomiting; central nervous system effects including sedation, euphoria, and delirium; pruritus; urinary retention; and more serious adverse effects such as respiratory depression.…”
mentioning
confidence: 99%
“…4,5 To improve postoperative pain relief, an integrative approach combining pharmacologic methods and various complementary nonpharmacologic analgesic techniques has been recommended. 6 Auricular acupuncture holds promise, as it is an easily performed technique that might be effective for treatment of both preoperative anxiety and postoperative pain in patients undergoing ambulatory surgery. 7,8 However, there are reasonable doubts in the scientific community concerning the specificity of acupuncture, 9 because the large randomized trials on auricular acupuncture for treatment of cocaine and alcohol dependence have found no difference between treatment and invasive needle control.…”
mentioning
confidence: 99%